Popular Reading in Academic Libraries: A Scoping Review - Lantz, Catherine; Insua, Glenda; Armstrong, Annie (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2026)
Objective – This scoping review examines the library literature on popular reading collections at academic libraries at both the secondary and post-secondary levels, with a focus on collection practices and characteristics, use, and impact.Methods – Researchers searched six databases for relevant literature from 1995 to the present. In addition to general article characteristics such as publication type, date, and location, the articles (both scholarly and popular) were analyzed for popular reading collection characteristics, activities related to popular reading collections, and implications for libraries.Results – The search identified 2,140 related records, 106 of which were chosen for inclusion in this review. The review found that popular reading collections are maintained by academic libraries worldwide, though the majority of articles were published in the United States and Canada. Circulation statistics are a common measure to gauge success, and graphic novels and other genre fiction are popular with students. Implications of popular reading collections revolved around their impact on students, library workflows, and campus collaborations.Conclusion – This study synthesized the library literature on popular reading collections, outlining their characteristics and impact on undergraduate students. Future research could help develop best practices for academic librarians working with popular reading collections.